Measuring enterprise architecture readiness at higher education institutions - Adam Sekti Aji; Tri Widodo (Association for Scientific Computing Electrical and Engineering, 2019)
This paper discusses the Enterprise Architecture (EA) implementation readiness measurement model. One of the definitions of EA is a framework or blueprint that an organization uses to achieve business goals by identifying important strategies, namely business, information, applications, and technology and their impact on business functions. Measuring the readiness of EA implementation in an institution is useful to reduce the potential losses due to failure of EA implementation. By identifying the supporting factors for the success of EA implementation, a measurement model for EA implementation readiness can be formulated and can be used as a reference to determine the readiness of an institution in EA implementation. The application of the model was carried out at two high education institutions with a different academic domain